Advantages and limitations of microtiter biofilm assays in the model of antibiofilm activity of Klebsiella phage KP34 and its depolymerase - Agnieszka Latka (Nature Portfolio, 2020)
Abstract One of the potential antibiofilm strategies is to use lytic phages and phage-derived polysaccharide depolymerases. The idea is to uncover bacteria embedded in the biofilm matrix making them accessible and vulnerable to antibacterials and the immune system. Here we present the antibiofilm efficiency of lytic phage KP34 equipped with virion-associated capsule degrading enzyme (depolymerase) and its recombinant depolymerase KP34p57, depolymerase-non-bearing phage KP15, and ciprofloxacin, separately and in combination, using a multidrug-resistant K. pneumoniae biofilm model. The most effective antibiofilm agents were (1) phage KP34 alone or in combination with ciprofloxacin/phage KP15, and (2) depolymerase KP34p57 with phage KP15 and ciprofloxacin. Secondly, applying the commonly used biofilm microtiter assays: (1) colony count, (2) LIVE/DEAD BacLight Bacterial Viability Kit, and (3) crystal violet (CV) biofilm staining, we unravelled the main advantages and limitations of the above methods in antibiofilm testing. The diverse mode of action of selected antimicrobials strongly influenced obtained results, including a false positive enlargement of biofilm mass (CV staining) while applying polysaccharide degrading agents. We suggest that to get a proper picture of antimicrobials’ effectiveness, multiple examination methods should be used and the results must be read considering the principle of each technique and the antibacterial mechanism.